The Consideration of Bid‘a Concept according to Saudi and Iranian Scholars (Mazahib, 2020)
The concept of innovation (bid'a) as a formative tool is used to create idiosyncratic nations depending on different scholars' interpretations, Wahhābīs in Saudi Arabia, and Shi'īs in Iran. Using the descriptive method throughout the paper, this article analyzes scholars' approaches towards bid'a concerning the sectarian interpretations and various legal methodologies. The extent of the relationship between the bid'a concept and the rulings related to the visitation of tombs, the practice of temporary marriage, and Nowrūz celebration will be the paper's primary focus. The interpretations and approaches of scholars towards bid'a have resulted in opposite solutions on these mentioned issues. The comparative conclusion aims to clarify the Saudi-Wahhābī and Iranian-Shi'ī scholars' principal attitudes towards the theoretical interpretation and practical application of the bid'a concept. The bid'a analysis attempts to introduce the operative purposes behind the rulings to answer which reasons impel the scholars functioning in these two countries from issuing the diametrically opposite views on controversial issues.Keywords: Islamic law, Saudi Arabia, Iran, Wahhabism, Ja'farism, Bid'a.